James Duff Brown: A Librarian Committed to the Public Library and the Subject Classification - de Sales, Rodrigo; Martínez-ávila, Daniel; Guimarães, José Augusto Chaves [UNESP] (IMR Press, 2021)
After two decades in the 21st Century, and despite all the advances in the area, some very important names from past centuries still do not have the recognition they deserve in the global history of library and information science and, specifically, of knowledge organization. Although acknowledged in British librarianship, the name of James Duff Brown (1862-1914) still does not have a proper recognition on a global scale. His contributions to a free and more democratic library had a prominent place in the works and projects he developed during his time at the libraries of Clerkenwell and Islington in London. Free access to the library shelves, an architecture centered on books and people, and classifications that are more dynamic were dreams fulfilled by Brown. With this biographical article, we hope to live up to his legacy and pay homage to a true librarian and an advocate of the public library and subject classification.
Keywords: James Duff Brown; open shelf system; public libraries; Subject Classification